Why does the "mental shotgun" fire system-justifying bullets?. Issue 5 (October 2014) - Gaucher, Danielle; Jost, John T.
Abstract We suggest that people privilege explanations relying on inherent rather than contingent factors not only because of an innate cognitive tendency to monitor reality, but because doing so satisfies the desire to perceive the societal status quo as legitimate. In support, we describe experimental studies linking the activation of system justification motivation to the endorsement of inherence-based (essentialist) explanations.